Rasim Özdenören hakkında bir soruşturma: Abdullah Harmancı, Abdullah Uçman, Ali Haydar Haksal, Ali Işık, Bahtiyar Aslan, Hasibe Çerko, Hayriye Ünal, Hüseyin Akın - Mantu, Uğur.
Türk Dili, 2022-4 (850, ekim 2022) 161-174 ss.